2021
DOI: 10.3390/app11209599
|View full text |Cite
|
Sign up to set email alerts
|

Actuating Performance Analysis of a New Smart Aggregate Using Piezoceramic Stack

Abstract: A new type of smart aggregate using piezoceramic stack (SAPS) was developed for improved output, as compared with a conventional smart aggregate with a single piezoceramic patch. Due to the better output, the proposed smart aggregate is preferred where the attenuating effect is strong. In this research, lead zirconate titanate (PZT) material in the form of discs was used due to its strong piezoelectric performance. For analysis, the proposed SAPS was simplified to a one-dimensional axial model to investigate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…The sizes of two plates are 400 mm × 250 mm × 1.5 mm and 400 mm × 200 mm × 1.5 mm, respectively. As illustrated in figure 3, two PZTs are also fixed on the two plates by epoxy glue for the excitation and reception of Lamb waves due to their excellent piezoelectric performance [48,49], wide bandwidth [50,51] and easy installment [52]. It should be noted that the location of the two PZT exciter and PZT receiver is selected randomly when the experiments are designed.…”
Section: Methodsmentioning
confidence: 99%
“…The sizes of two plates are 400 mm × 250 mm × 1.5 mm and 400 mm × 200 mm × 1.5 mm, respectively. As illustrated in figure 3, two PZTs are also fixed on the two plates by epoxy glue for the excitation and reception of Lamb waves due to their excellent piezoelectric performance [48,49], wide bandwidth [50,51] and easy installment [52]. It should be noted that the location of the two PZT exciter and PZT receiver is selected randomly when the experiments are designed.…”
Section: Methodsmentioning
confidence: 99%
“…The previous discussion focused on the development of Smart Aggregates (SAs) in terms of dimensionality, where transducers with a single piezoelectric layer were commonly used. However, the improvements in sensing range and output power of these transducers were often overlooked until Lu [68] introduced a novel SA design using piezoelectric stacks. Several experimental results have confirmed that SAs incorporating piezoelectric stacks exhibit increased sensitivity compared to traditional ones, making them promising for structural health monitoring applications in civil engineering [26,27,68].…”
Section: Sas With Piezoelectric Stacks (Saps)mentioning
confidence: 99%
“…Such a unique stack configuration can achieve very high power characteristics [35,36], and they have been widely used in various applications, such as ultrasonic transducers [37,38], fuel injectors [39,40], and quantitative corrosion measurement probes [41]. Recent studies have also shown that they can better enhance the sensing range when the attenuating effect is strong [42,43].…”
Section: Introductionmentioning
confidence: 99%